Coordination and Redox Isomerization in the Reduction of a Uranium(III) Monoarene Complex1. Issue 28 (30th May 2014) - La Pierre, Henry S.; Kameo, Hajime; Halter, Dominik P.; Heinemann, Frank W.; Meyer, Karsten
Abstract Synthetic studies on the redox chemistry of trivalent uranium monoarene complexes were undertaken with a complex derived from the chelating tris(aryloxide)arene ligand (Ad, MeArO)3mes3−. Cyclic voltammetry of [{(Ad, MeArO)3mes}UIII] (1) revealed a nearly reversible and chemically accessible reduction at −2.495 V vs. Fc/Fc+—the first electrochemical evidence for a formally divalent uranium complex. Chemical reduction of 1 indicates that reduction induces coordination and redox isomerization to form a uranium(IV) hydride, and addition of a crown ether results in hydride insertion into the coordinated arene to afford uranium(IV) complexes. This stoichiometric reaction sequence provides structural insight into the mechanism of arene functionalization at diuranium inverted sandwich complexes.